98.8k views
2 votes
Can someone please show me step by step for this system of equations? (Number 5)

Can someone please show me step by step for this system of equations? (Number 5)-example-1

1 Answer

4 votes

Answer:

x = 3, y = -1, z = -4

Explanation:

2x + y - z = 9 (1)

- x + 6y + 2z = -17 (2)

5x + 7y + z = 4 (3)

(3) + (1)

7x + 8y = 13 (4)

2 × (1)

4x + 2y - 2z = 18 (5)

(5) + (2)

3x + 8y = 1 (6)

(4) - (6)

4x =12

x = 3

substitute x = 3 in (6)

9 + 8y = 1

8y = -8

y = -1

substitute x = 3 and y = -1 in (1)

2 × 3 + (-1) - z = 9

6 - 1 - z = 9

5 - z = 9

z = 5 - 9

z = -4

User Gbt
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.